The Influence of Attitude and Trust in Green Banking on Customer Interest in Opening an Account: Case Study of PT Bank Central Asia Tbk - Permana, Frianka Bagja; Hidayah, Riski Taufik (Eastasouth Institute, 2025)
This study aims to analyze the factors that influence customer interest in using green banking services, specifically when opening an account at BCA. Using a quantitative approach and the SEM-PLS method with a sample of 385 respondents, the study found that the variables Green Perceived Value, Green Trust, Environmental Concern, Perceived Consumer Effectiveness, Perceived Environmental Integrity, and Collectivism have a significant effect on Green Purchase Intention. Meanwhile, Green Perceived Risk does not show a significant effect. This finding confirms the importance of environmental values and trust in encouraging the adoption of sustainable banking services.